Maktabah Samilah as A "Digital Library" to Meet the Information Needs of Muslims - Muhamad Farhan; Ahmad Reza Alpha Pahlevi (Journal of Islamic Studies & Social Science, 2024)
The rapid development of the digital world has entered an era of disruption, which has an impact on various sectors, including education. In Indonesia, digital transformation is considered important for the advancement of education, enabling cost efficiency, increased productivity, and better quality of education. One aspect of digital transformation in education is the adoption of digital libraries. Digital libraries are a replacement for manual systems in managing and accessing information, allowing users to access collections in digital format through computers. The digital library's collection includes a variety of document formats, such as text and images, as well as video recording media. One example of a popular digital library is Maktabah Syamilah, which provides thousands of books in various fields of Islamic scholarship. This program provides easy access and information search for users, especially students and researchers in the field of Islam. The use of Maktabah Syamilah has had a positive impact on the development and access to Islamic literature. However, in adopting a digital library, it is necessary to consider effective collection management strategies and efforts to meet the needs of quality information. Thus, digital libraries such as Maktabah Syamilah can be an efficient solution in meeting information needs in today's digital era.